The Influence of Talent Management, Work-Life Balance and Organizational Commitment on Employee Performance Through Job Satisfaction in Batam City Distribution Sector - Sentoso, Antony; Febrianti, Febrianti; Nelson, Alden (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study seeks to determine the impact of talent management, work-life balance, and organizational commitment on employee performance, with satisfaction serving as a mediating variable. In Batam City, the distribution sector experiences fierce rivalry, necessitating enterprises to secure high-performing staff. This study employs a quantitative descriptive methodology utilizing sampling procedures via questionnaires. The analysis method used was SEM-PLS, with 250 respondents from the distribution sector in Batam City. This research tested five variables with 19 questions which were measured using outer loading, reliability and validity. This research indicates that Talent Management (X1), Work-Life Balance (X2), and Organizational Commitment (X3) significantly influence Employee Performance (Y2) via Job Satisfaction (Y1).